1977
DOI: 10.1007/bf00384815
|View full text |Cite
|
Sign up to set email alerts
|

On the use of the scrotum for feeding larval ixodid ticks on hosts

Abstract: The efficacy of feeding larval stages of Amblyomma variegatum, Hyalomma rufipes and Boophilus decoloratus on the ears and scrotum of sheep is compared. The effect of age of larvae on the number that engorged on the animal was also investigated. A significantly greater number of larvae fed on scrotum than on ears. The greatest number of larvae engorged when they were fed on the scrotum or ear within 1-4 days of hatching. The older the larvae, the less the number that fed. The economic advantages of adopting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Larval smears were made daily for six (6) days and in fact by the 5th day detection of vermicules had become difficult. Mahoney and Mirre (5) as well as Ogunji and Dipeolu (6) showed that larval ticks would feed best within the first 4 days of life, after which those that did not feed were not likely to feed again.…”
Section: Discussionmentioning
confidence: 99%
“…Larval smears were made daily for six (6) days and in fact by the 5th day detection of vermicules had become difficult. Mahoney and Mirre (5) as well as Ogunji and Dipeolu (6) showed that larval ticks would feed best within the first 4 days of life, after which those that did not feed were not likely to feed again.…”
Section: Discussionmentioning
confidence: 99%